2016
DOI: 10.1186/s12878-016-0051-y
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of chronic lymphocytic leukemia in Senegal

Abstract: BackgroundChronic lymphocytic leukemia (CLL) is a mature B-cell neoplasm characterized by the expansion of CD5-positive lymphocytes in peripheral blood. While CLL is the most common type of leukemia in Western populations, the disease is rare in Africans. Hence, clinical and laboratory data and studies of CLL in Sub Saharan populations have been limited. The aims of this study were to analyze the characteristics of senegalese patients with CLL at the time of the diagnosis and to identify the correlation betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
14
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 28 publications
7
14
4
Order By: Relevance
“…However, Sall et al study reported that lymphocyte count was signi cantly greater in patients with stage C than groups with stages A or B(24). Furthermore, Ahmed et al in a study reported that there was not signi cant associated between CBC results and advanced Rai stage(25).Although Bakouny et al did not nd signi cant relation between PLR with the survival of CLL patients(26), there was a negative association between PLR and advanced clinical stages of CLL in our study. Taken together, we can hypothesis that PLR can act as a prognostic biomarker in CLL patients which requires further investigation.…”
contrasting
confidence: 70%
“…However, Sall et al study reported that lymphocyte count was signi cantly greater in patients with stage C than groups with stages A or B(24). Furthermore, Ahmed et al in a study reported that there was not signi cant associated between CBC results and advanced Rai stage(25).Although Bakouny et al did not nd signi cant relation between PLR with the survival of CLL patients(26), there was a negative association between PLR and advanced clinical stages of CLL in our study. Taken together, we can hypothesis that PLR can act as a prognostic biomarker in CLL patients which requires further investigation.…”
contrasting
confidence: 70%
“…A median age of 56 was recorded in patients with CLL in this cohort, which again compares to higher ages of 65-70 years in European and Northern American publications [12,13,14]. This younger age appears to correlate with an emerging pattern in African patients with average ages at onset of 56, 55 and 61 in Nigerian, Ethiopian and Senegalese cohorts respectively [15,16,17]. Unlike in MM however, younger age at presentation has also been reported in black patients in high income settings [18].…”
Section: Age At Presentationsupporting
confidence: 57%
“…Similarly, Basabaeen et al showed that thrombocytopenia was significantly correlated with splenomegaly [24]. However, Sall et al study reported that lymphocyte count was significantly greater in patients with stage C than groups with stages A or B [25]. Furthermore, Ahmed et al in a study reported that there was not significant associated between CBC results and advanced Rai stage [26].…”
Section: Discussionmentioning
confidence: 93%